Scholars' Views on the Construction of Interpretation in the Era of Prophethood - Aria Panji Saputra; Muhammad Taufiq (Electronic Journal of Education, Social Economics and Technology, 2025)
ABSTRACT Rasulullah SAW is the lover of Allah SWT who was given the task by him to receive revelations, convey and explain the revelations he conveyed to his people. There are verses in the Qur'an that are clear and unclear, and as for verses that are not clear, interpretation is really needed so that you can draw guidance or lessons from verses that are not clear or are still unclear. When the Al-Qur'an was revealed by Allah SWT to Rasulullah SAW, Rasulullah immediately conveyed the revelation to his friends and if there was something that the friends did not understand about the verse, Rasulullah would immediately interpret it for him, however, there were differences of opinion among the scholars regarding There are those who interpret the verses as interpreted by the Prophet as a whole and there are also those who think in part. The research method that the author uses in this research is library research. And the results of this research are differences in opinion among scholars regarding the construction of interpretation in the era of Rasulullah, namely that there are some scholars, one of whom is Ibn Taymiyah, who believes that Rasulullah interpreted the verses of the Qur'an entirely for his companions and some scholars also argue that Rasulullah interpreted some for his companions.KEY WORDS: Ulama, construction, interpretation, Rasulullah